Research on rehabilitation assessment methods based on human gait and sEMG. Issue 1 (31st December 2016) - Chen, Kun; Huang, Xinyu; Zhang, Yanan; Ai, Qingsong
Abstract: Based on the study of human gait, the rehabilitation assessment indicators which can comprehensively reflect the motor function of lower limbs are summed up, including muscle force, range of motion, stride length and gait speed. Then the surface electromyography (sEMG) acquisition equipment and kinematics data acquisition equipment are used to collect the EMG data and kinematic data in real time during subjects' walking process, and the statistical analysis method is used to verify the rationality of the selected assessment indicators. By using analytic hierarchy process, the weight of each evaluation index is determined, and finally a relatively scientific, accurate and objective rehabilitation evaluation model is formed. The model can be used to assess the lower limb motor function of subjects through the quantitative index, overcoming the high subjectivity and low sensitivity of the clinical rehabilitation physician assessment.